Solar cycle response and long‐term trends in the mesospheric metal layers. Issue 7 (27th July 2016) - Dawkins, E. C. M.; Plane, J. M. C.; Chipperfield, M. P.; Feng, W.; Marsh, D. R.; Höffner, J.; Janches, D.
Abstract: The meteoric metal layers (Na, Fe, and K)—which form as a result of the ablation of incoming meteors—act as unique tracers for chemical and dynamical processes that occur within the upper mesosphere/lower thermosphere region. In this work, we examine whether these metal layers are sensitive indicators of decadal long‐term changes within the upper atmosphere. Output from a whole‐atmosphere climate model is used to assess the response of the Na, K, and Fe layers across a 50 year period (1955–2005). At short timescales, the K layer has previously been shown to exhibit a very different seasonal behavior compared to the other metals. Here we show that this unusual behavior is also exhibited at longer timescales (both the 11 year solar cycle and 50 year periods), where K displays a much more pronounced response to atmospheric temperature changes than either Na or Fe. The contrasting solar cycle behavior of the K and Na layers predicted by the model is confirmed using satellite and lidar observations for the period 2004–2013. Key Points: First study of response of modeled metal layers to changing atmosphere K is the only metal to exhibit pronounced response to atmospheric changes at 11 year solar cycle and longer‐term (50 year) timescales K layer may be good candidate as a sensitive indicator of long‐term changes in the mesosphere/lower thermosphere region